Parental Resilience and Quality of Life in Children with Developmental Disabilities in Indonesia: The Role of Protective Factors - Widyawati, Yapina; Scholte, R.H.J; Kleemans, Tijs; Otten, Roy (Journal of developmental and physical disabilities, 2023)
The severity of physical, cognitive, and social-emotional challenges in children with developmental disabilities significantly impacts their quality of life. One of the most consistent factors that play a role in the quality of life for children with a developmental disability is parental resilience. Previous research has identified several factors that influence parental resilience. However, this research is limited to Western countries. Little is known about the role of these factors in relation to parental resilience in Asian societies. The present study investigates the longitudinal associations between potential protective factors (fewer stressors, adaptive appraisal, social support, and compensating experiences) and parental resilience and quality of life in Indonesian families with children with developmental disabilities. A three-wave longitudinal design was used to test the indirect link between protective factors, family resilience, and quality of life. Wave one was composed of 497 families, out of which 224 and 209 families participated in waves two (1-year follow-up) and three (2-year follow-up), respectively. The Inventory of Family Protective Factors (IFPP), the Parenting Resilience Elements and the Quality of Life of children scales were used to assess the main concepts. The longitudinal connections between protective variables, parental resilience, and children’s quality of life were tested using cross-lagged path analysis. The results showed that all protective factors predicted parental resilience, and parental resilience predicted the quality of life of children with developmental disabilities.